3s-4=2s+3

Simple and best practice solution for 3s-4=2s+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3s-4=2s+3 equation:


Simplifying
3s + -4 = 2s + 3

Reorder the terms:
-4 + 3s = 2s + 3

Reorder the terms:
-4 + 3s = 3 + 2s

Solving
-4 + 3s = 3 + 2s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-2s' to each side of the equation.
-4 + 3s + -2s = 3 + 2s + -2s

Combine like terms: 3s + -2s = 1s
-4 + 1s = 3 + 2s + -2s

Combine like terms: 2s + -2s = 0
-4 + 1s = 3 + 0
-4 + 1s = 3

Add '4' to each side of the equation.
-4 + 4 + 1s = 3 + 4

Combine like terms: -4 + 4 = 0
0 + 1s = 3 + 4
1s = 3 + 4

Combine like terms: 3 + 4 = 7
1s = 7

Divide each side by '1'.
s = 7

Simplifying
s = 7

See similar equations:

| 3v+7=22 | | 2e-(e-7)=12 | | 3c+5=8 | | 2b+8=22 | | 6a+20=9a-36 | | 3y+4=7 | | 10x=(8x+32) | | 2a+5=21 | | 8t=-68 | | 3x^2+10x-7=0 | | 2u+5=25 | | 4(5x+2)-4=0 | | 3x^2-15x=-6 | | X+89= | | 7a=4-b | | 4-5x=444 | | 4x^2-3+8=0 | | 5(s+9)-52= | | 2x*3x=144 | | X+109= | | 15x-5y=26 | | 22+6p=4+12p | | 49x^2-26X+36=0 | | 8x-6=9x+2 | | 5x^2+39x-54=0 | | 18=11y-8y | | N+0.48=12.7 | | 24x-1= | | -2x-2x=31-7 | | x^3+12x^2+32x=0 | | -5+(-15+1)=2(7d-16)-d | | 20x+5= |

Equations solver categories